Factors Affecting Work Performance and Empowerment Efforts among Indonesian Domestic Workers in Recipient Countries (Journal of Governance and Development (JGD), 2014)
Development of globalization, on the one hand, opens up opportunity for women to make international migration to be a Domestic Worker in a recipient country. This study analyzes the factors that affect job performance and what domestic workers and stakeholders need to do in empowering of domestic workers in receiving countries. The research was conducted in the Klang Valley of Malaysia. The study used a qualitative approach, with in-depth interview techniques and documentary techniques, through the â€œInteractive Data Analysisâ€. The results showed the main factors that affect work performance of women migrant domestic workers are two, namely; (1) internal factors: (a) domestic socio-economic background is not good, cause moral / behavioral MDW less support their work performance, (b) morality domestic workers also show poor results, (c) relatively good hard skills, soft skills but still low; (2) external factors: (a) the working conditions in the employerâ€™s premises is not the dominant factor causing the quality of domestic job performance,(b) the role of the Government of Indonesia in the empowerment of domestic workers, show lack of empowerment of domestic workers in receiving countries.